Global Knowledge Structures and Thematic Evolution of Community Empowerment Research: A Bibliometric Analysis of Scopus-Indexed Publications (2016–2024) - Luthfi Ilham Ramdhani; Muchlas Suseno; Aip Badrujaman; Riyan Arthur; Irwanto (LPPM Undiksha, 2026)
Community empowerment has emerged as a strategic paradigm in sustainable development, participatory governance, and knowledge-based social transformation. Despite the growing global volume of studies on community empowerment, comprehensive mapping of its intellectual structure, collaboration patterns, and thematic evolution remains limited. This study aims to map the global intellectual landscape of community empowerment research through a bibliometric analysis of Scopus-indexed journal publications published between 2016 and 2024. A total of 460 articles were analyzed using quantitative bibliometric methods supported by Biblioshiny (R) and VOSviewer. The findings reveal a strong annual growth rate of 10.77%, indicating a dynamically expanding and increasingly consolidated research field. Dominant research themes include community participation, public health, sustainability, collaborative governance, and participatory leadership, accompanied by a clear shift toward evidence-based approaches, social innovation, and digitally mediated empowerment models. International collaboration patterns demonstrate a core–periphery structure, with the United Kingdom, the United States, and Australia serving as central hubs, alongside rapidly increasing contributions from Global South countries, particularly Indonesia. The findings suggest that integrative policy frameworks linking higher education, research, and community engagement can significantly enhance global scholarly visibility and collaborative capacity. Community empowerment has evolved into a multidimensional knowledge system with substantial implications for academic research, policymaking, and community-oriented sustainable development practices.